Recommendations for intra-abdominal infections consensus report - Avkan-Oguz, Vildan; Baykam, Nurcan; Sokmen, Selman; Guner, Rahmet; Agalar, Fatih; Alp, Emine; Koksal, Iftihar (Aves, 2016)
Guidelines include the recommendations of experts from various specialties within a topic in consideration of data specific to each country. However, to date there has not been a guideline standardizing the nomenclature and offering recommendations for intra-abdominal infections (IAIs) in Turkey. This is mainly due to the paucity of laboratory studies regarding the clinical diagnosis and treatment of IAIs or the sensitivity of microorganisms isolated from patients with IAIs. However, due to the diversification of host characteristics and advancements in technological treatment methods, it has become imperative to 'speak a common language'. For this purpose May 2015, a group of 15 experts in intra-abdominal infections, under the leadership of the Infectious Diseases and Clinical Microbiology Specialty Society of Turkey (EKMUD) and with representatives from the Turkish Surgical Association, Turkish Society of Colon and Rectal Surgery, Hernia Society, Turkish Society of Hepato-pancreato-biliary Surgery, and the Turkish Society of Hospital Infections and Control, was formed to analyze relevant studies in the literature. Ultimately, the suggestions for adults found in this consensus report were developed using available data from Turkey, referring predominantly to the 2010 guidelines for diagnosing and managing complicated IAIs in adults and children by the Infectious Diseases Society of America (IDSA) and the Surgical Infection Society. The recommendations are presented in two sections, from the initial diagnostic evaluation of patients to the treatment approach for IAI. This Consensus Report was presented at the EKMUD 2016 Congress in Antalya and was subsequently opened for suggestions on the official websites of the Infectious Diseases and Clinical Microbiology Specialty Society of Turkey and Turkish Surgical Association for one month. The manuscript was revised according to the feedback received.
Keywords: Diagnosis; guide; intra-abdominal infection; management; recommendations